CONCEPTUALIZATION OF THE PHILOSOPHICAL TEXT IN THE STRUCTURES OF FOREGROUNDING - Shamshurin, A.A. (Bulletin of Udmurt University. Series Philosophy. Psychology. Pedagogy, 2021)
The foregrounding of the text goes from a potential, not yet existing text to its relevance. In this march, the philosopher coincides with the philosophical text. This coincidence can be called a fore-text, which allows you to "enter" a philosophical text. The Internet considers hypertext as an informational formless set of texts, which is predetermined for the subject. The posed problem concerns the possibility of the presence of the subject in a digital hypertext. The aim of the study is to set the philosophical text as a concept, showing the subjectivation of the text with the help of the developed concept of a fore-text. To achieve the expected result, it is necessary to consider the history of philosophy as a chronological coherent sequence of texts, which is assumed as a context or common meaning. The problem is complicated by the fact that a single history of philosophy does not exist in digital space. It resides as a plurality of authors' histories of philosophy. The "introduction," "preface," etc. to a philosopher's text then becomes a "substitute" for the lost context. The development of the subjectivity of philosophy shows that the fore-text becomes the text itself. This development corresponds to the conceptualization of philosophy and its liberation from the authority of antiquity as traditionalism. Under the conditions of virtual reality and hypertext information, only conceptualization preserves the human in man - thinking. The author of the article poses the questions: "So what have we lost by asserting the end of the history of philosophy? Isn't the "new" pre-structure of the philosophical text the actualized "hyper-conceptual" space of the Internet?"